Kebijakan Hukum Pidana Bagi Anak yang Melakukan Pengulangan Tindak Pidana - Kahfi Parsa (Publikasi Indonesia, 2023)
Supporting documents and statements of appearers are the criminal responsibility for children as repeat offenders. Know the legal policies for children who commit repeated crimes and know if the law given is not based on the Law on the Juvenile Justice System but on the Criminal Code. This research is included in the type of normative research supported by juridical data which basically uses a normative legal approach with the addition of various juridical elements regarding the implementation of normative legal provisions (laws). The object of this research is normative legal research, namely research conducted by collecting legal materials in the form of books and texts of laws and regulations. The text of the legislation in question is Law 11 of 2012 concerning the Juvenile Criminal Justice System which explicitly regulates diversion which is the object of this research. The results of the study show that legal policies for children who commit repeated crimes by resolving cases of children who commit repeated crimes (Recidive) using the diversion pathway are carried out using the provisions of the SPPA Law, namely by penal mediation. Penal mediation is used in the early stages when there is a desire by the child to solve the problem, which is accompanied by related parties, namely parents, victims and their families, community leaders, and mediators in leading the forum. The principle of legal protection for children must be in accordance with the Convention on the Rights of the Child as ratified by the government of the Republic of Indonesia with Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child (Convention on the Rights of the Child). Children's Rights). Legal protection for children who repeat criminal acts and those who commit criminal offenses with a sentence of more than 7 (seven) years by seeking diversion.